FSR 1716: a new Milky Way globular cluster confirmed using VVV RR Lyrae stars - Minniti, Dante; Dékány, István (The astrophysical journal. Part 2, Letters, 2017)
We use deep multi-epoch near-IR images of the VISTA Variables in the Vía Láctea (VVV) Survey to search for RR Lyrae stars toward the Southern Galactic plane. Here, we report the discovery of a group of RR Lyrae stars close together in VVV tile d025. Inspection of the VVV images and PSF photometry reveals that most of these stars are likely to belong to a globular cluster that matches the position of the previously known star cluster FSR 1716. The stellar density map of the field yields a >100σ detection for this candidate globular cluster that is centered at equatorial coordinates R.A. J 2000 = 16:10:30.0, decl. J 2000 = −53:44:56 and galactic coordinates l = 329.77812, b = −1.59227. The color-magnitude diagram of this object reveals a well-populated red giant branch, with a prominent red clump at K s = 13.35 ± 0.05, and J − K s = 1.30 ± 0.05. We present the cluster RR Lyrae positions, magnitudes, colors, periods, and amplitudes. The presence of RR Lyrae indicates an old globular cluster, with an age >10 Gyr. We classify this object as an Oosterhoff type I globular cluster, based on the mean period of its RR Lyrae type ab, ##IMG## [http://ej.iop.org/images/2041-8205/838/1/L14/apjlaa5881ieqn1.gif] $\langle P\rangle =0.540$ days, and argue that this is a relatively metal-poor cluster with [Fe/H] = −1.5 ± 0.4 dex. The mean extinction and reddening for this cluster are ##IMG## [http://ej.iop.org/images/2041-8205/838/1/L14/apjlaa5881ieqn2.gif] $A_K_s=0.38± 0.02$ and E ( J − K s ) = 0.72 ± 0.02 mag, respectively, as measured from the RR Lyrae colors and the near-IR color-magnitude diagram. We also measure the cluster distance using the RR Lyrae type ab stars. The cluster mean distance modulus is ( m − M ) 0 = 14.38 ± 0.03 mag, implying a distance D = 7.5 ± 0.2 kpc and a Galactocentric distance R G = 4.3 kpc.